2020
DOI: 10.1144/sp503-2020-37
|View full text |Cite
|
Sign up to set email alerts
|

Early­­­­–Middle Ordovician sedimentation and bimodal volcanism at the margin of Iapetus: the Trollhøtta–Kinna Basin of the central Norwegian Caledonides

Abstract: The late Neoproterozoic to Palaeozoic Iapetus Ocean developed between Laurentia, Baltica, Siberia and Gondwana. Its Palaeozoic closure history is recorded by volcano-sedimentary successions within the Caledonian orogen of Scandinavia, the British Isles and Newfoundland. We present new lithological, geochemical and geochronological data relevant for the Iapetan closure history from the hitherto poorly known Trollhøtta-Kinna basin (central Norwegian Caledonides). This basin consists of alternating siliciclastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…There is no systematic difference between samples from the southern and northern deposits. The highly enriched mafic to intermediate volcanic rocks of the Kinna volcanic succession ( Dalslåen et al, 2020a) and the MORBlike basalts from the Trollhøtta unit (Dalslåen et al, 2020b) Unfortunately, the volcanic rocks we separated (with up to 137 ppm of Zr) did not contain zircon, monazite or other heavy minerals that could have provided an age of volcanism. To obtain at least a maximum depositional age of the Skuggliberga unit, two sandstone samples were selected for detrital zircon analysis.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…There is no systematic difference between samples from the southern and northern deposits. The highly enriched mafic to intermediate volcanic rocks of the Kinna volcanic succession ( Dalslåen et al, 2020a) and the MORBlike basalts from the Trollhøtta unit (Dalslåen et al, 2020b) Unfortunately, the volcanic rocks we separated (with up to 137 ppm of Zr) did not contain zircon, monazite or other heavy minerals that could have provided an age of volcanism. To obtain at least a maximum depositional age of the Skuggliberga unit, two sandstone samples were selected for detrital zircon analysis.…”
Section: Resultsmentioning
confidence: 91%
“…The mapping by Dalslåen et al (2020b) showed that large parts of what was previously assigned to the Hovin Group, particularly in the Gisnadalen and Skjørstadhovden-Stølen areas (Fig. 2A), are turbiditic rocks intercalated with Trollhøtta metavolcanic rocks.…”
Section: Accepted Manuscriptmentioning
confidence: 78%
See 3 more Smart Citations